Impact of solidarity economy education on solidarity actions by alumni of the universidad cooperativa de colombia dental school in pasto (Revista Nacional de Odontología, 2014)
Introduction: This article presents the research project entitled “Impact of Solidarity Economy Education on Solidarity Actions by Alumni of the Universidad Cooperativa de Colombia Dental School in Pasto” which was completed in 2011 by the Dental Research Group (Grupo de Investigaciónes en Odontología, giod) at the Pasto campus of the Universidad Cooperativa de Colombia.Methods: A cohort of dentists from that university was compared with other Dental School alumni from 2002 to 2010. Information on dentists’ demographic and socio-economic variables, leadership skills, participation in solidarity economy organizations and enterprise creation was obtained by a self-administered questionnaire. The statistical analyses were performed using spss 17 version.Results: This study shows that there were no statistical differences between the two cohorts according to demographic and socio-economic variables. 7.7% had leadership skills. The entire cohort pointed to meaning (21.2%) and membership (20.2%) as principal Personal Leadership Scale components. 66.7% of dentists graduated from our university participated in solidarity economy organizations, while a similar percentage of alumni from other dental schools were involved in enterprise creation.Conclusions: The results of this research indicate that it is imperative that this university design strategies to increase leadership skills and improve solidarity economy courses in the odontology curriculum.
Keywords: economics; continuing dental education; leadership; odontology; private sector.